On the WordMortgageas Signifier of Bliss with respect to Time inEl perseguidor[The Pursuer]: a Psychoanalytical InterpretationAbstract (2016)
Literary criticism has pointed out that El perseguidor is about the crisis of an artist, Johnny Carter. Nevertheless, based on psychoanalysis, as a discipline in charge of studying the unconscious, it may be appreciated that this musician is traversed by troubles stemming from the unconscious, from which may be derived specific aspects for understanding the words, attitudes, actions and reactions of this charac ter. The aim of this study is to offer an interpretation that illustrates certain features of this problem and helps to clarify the being of the artist-subject. In order to do this, the present text presents the relation between signifier and body from a psychoanalytical perspective, as elements for an alternative reading of The Pursuer by Julio Cortázar. The purpose is to refer to how a signifier, a word, touches the subject’s body and runs through it and puts him in a state of bliss or jouissance . In the case of “The pursuer”, the word mortgage puts the subject in a state of bliss with respect to time. This implies delving into the matter of bliss [jouissance] and what subject we are referring to, in the case of the musician: a subject in an ongoing crisis due the incidence of the signifier